Penyuluhan ASI Eksklusif Dengan Kejadian Stunting Pada Usia Balita (1 - 5 Tahun) Di Desa Kalikoa Kecamatan Kedawung Kabupaten Cirebon - Sofiyati Sofiyati (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
This service aims to provide education regarding knowledge and understanding about exclusive breastfeeding which is linked to the incidence of stunting in toddlers. Exclusive breast milk is the best food for babies. Exclusive breastfeeding provides benefits to both mother and baby. The advantage of exclusive breastfeeding is that it creates a bond of love between the mother and baby. The benefits of breast milk, apart from improving optimal health and intelligence, breast milk also have a good impact on children's emotions, spiritual maturity, and good social development. Based on the results of the health education that has been carried out, the evaluation obtained is that all mothers who have children under five in Kalikoa Village, Tengah Tani District, Cirebon Regency have attended health education and are able to: state the meaning of exclusive breastfeeding, mention the benefits of exclusive breastfeeding, explain the pattern of giving exclusive breast milk, state understanding and causes of stunting, explaining the meaning of toddlers, explaining preventing stunting in toddlers, analyzing the relationship between exclusive breastfeeding and the incidence of stunting in toddlers, implementing the knowledge gained in everyday life.